2022
DOI: 10.1038/s41467-022-31876-2
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity-dependent profiling of RNA 5-methylcytidine dioxygenases

Abstract: Epitranscriptomic RNA modifications can regulate fundamental biological processes, but we lack approaches to map modification sites and probe writer enzymes. Here we present a chemoproteomic strategy to characterize RNA 5-methylcytidine (m5C) dioxygenase enzymes in their native context based upon metabolic labeling and activity-based crosslinking with 5-ethynylcytidine (5-EC). We profile m5C dioxygenases in human cells including ALKBH1 and TET2 and show that ALKBH1 is the major hm5C- and f5C-forming enzyme in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 76 publications
1
37
1
Order By: Relevance
“…ALKBH1 was reported, in 2022, to determine minor modification sites also in lncRNAs. However, it was reported that the main function of ALKBH1 is exerted on tRNAs ( 47 ).…”
Section: M5c Modificationmentioning
confidence: 99%
“…ALKBH1 was reported, in 2022, to determine minor modification sites also in lncRNAs. However, it was reported that the main function of ALKBH1 is exerted on tRNAs ( 47 ).…”
Section: M5c Modificationmentioning
confidence: 99%
“…Ketenes are high-energy motifs that serve as useful electrophilic traps in biologically relevant environments. [62,84] The ability to access them via bioorthogonal reagents provides a blueprint for a variety "chemically triggered" processes. In one area, we have been leveraging selective ketene formation for biomolecule crosslinking.…”
Section: Phosphines and Cpos For Transformations Beyond A Classic Lig...mentioning
confidence: 99%
“…The group of Kleiner applied this principle for RNA‐mediated activity‐based protein profiling by feeding HEK293T cells with 5‐ethynylcytidine, which gets incorporated into cellular RNA [69] . Protein‐RNA enrichment and quantitative mass spectrometry proteomics showed that the Fe(II)‐α‐KG‐dependent dioxygenase ALKBH1 is the major m5C‐oxidizing enzyme in HEK293T cells, where it is largely responsible for the production of hm 5 C and f 5 C of within RNA.…”
Section: Introductionmentioning
confidence: 99%